Research traceability identification talent in sports psychology: a bibliometric analysis with vosviewer - Mona Fiametta Febrianty; Komarudin Komarudin; Geraldi Novian; Xuan Quynh Lai (Jurnal Patriot, 2026)
Problems: Talent identification in sports is a multidimensional field of research that continues to evolve in line with advances in science, technology, and the needs of modern sports. Talent identification encompasses not only physical aspects and tactical skills but also psychological, social, cognitive, and environmental factors. Despite the increasing research, mapping global research trends, particularly on psychological skill-based talent identification in sports, remains a lack of a comprehensive structure. Purpose: This study aims to analyze the mapping of global research trends regarding psychological skills-based talent identification in sports, evaluate scientific collaboration networks, identify existing research gaps, and compile recommendations for future research. Methods: This study employed bibliometric analysis with the help of VOSviewer software. Data sources were obtained from Google Scholar for the 2015–2025 period through the Publish or Perish Reference Manager application. Mapping was conducted based on frequently appearing and interrelated keywords in the scientific literature, namely "Talent Identification by Psychological Skills in Sport," which resulted in 500 documents with a topical scope that reflects the diversity of themes in the field being studied. Results: The research results show that the peak number of publications occurred in 2016, indicating increased interest in this topic during that period. The most frequently published journal was Psychology of Sport and Exercise, published by Elsevier. Conclusion: This study provides a comprehensive overview of the development of talent identification research in sports from a psychological perspective and can be a starting point for further researchers in finding relevant sources and theoretical foundations, as well as identifying research opportunities that are still open in the future